Harnessing Liposomes for Advanced Gene Therapy: A Comprehensive Review - Sai Phanindra Vemuri; Prasad Karnati; Kolathur Pandyan Vadayar; Priya Singh (Journal of Bio-X Research)
Gene therapy, a revolutionary approach to treating genetic disorders, aims to introduce functional genes into cells to correct genetic defects. Liposomes, artificial lipid vesicles, have emerged as promising nonviral vectors for gene delivery. Owing to their biocompatibility, versatility, and ability to encapsulate various therapeutic molecules, liposomes are ideal candidates for gene therapy. This review explores the principles of liposome-based gene therapy, including composition, mechanisms of action, and applications. We discuss the challenges and limitations of liposome-mediated gene delivery and ongoing research efforts to improve their efficacy and safety. In conclusion, liposomes offer a promising avenue for developing effective and safe gene therapies for various genetic diseases.